(untitled) (Web of Teachers: Inderscience Research, 2024)
Developing oral communication competence is a vital component of higher education, particularly for non-philological students who may not receive formal linguistic training. This paper explores the significance of fostering effective speaking skills and the pedagogical approaches that can enhance oral communication abilities in non-philological students. Emphasis is placed on interactive teaching methods, role-playing, and feedback mechanisms that encourage participation and reduce communication apprehension. The study highlights the importance of integrating communication skill development across various disciplines to equip students with the necessary tools to succeed academically and professionally.